How clinical and research failures lead to suboptimal prescribing: the example of chronic gout. (1st December 2011) - Lipworth, Wendy; Kerridge, Ian; Brett, Jonathan; Day, Richard
Abstract : Despite the existence of several effective drugs for chronic tophaceous gout, management is often neither rational nor effective. Wendy Lipworth and colleagues examine the possible reasons